Discourses shaping human rights education research in South Africa: Future considerations - Simmonds, S.; du Preez, P. (South African Journal of Higher Education, 2017)
Human rights education is critiqued for being traditionalist and conceptually imprisoned. This view stems from the distrust in its ability to transform deeply rooted injustices and inequalities etched within South Africa’s society. There is therefore an outcry to reimagine human rights education. For this article it is important to understand how and why human rights education discourses in South Africa have come to be framed by some scholars in this way and to contemplate where the discourse might be heading in the future. We reviewed doctoral theses in the field of Education which claim to engage with and make contributions to human rights education research. We found that human rights education discourses have been (and are being) shaped in South Africa in terms of three distinct phases: inception, growth, and cynicism. It became evident from the findings that human rights education research is predominantly school-based and fundamentally descriptive and uncritical. To conclude, we reflect on these findings so as to put forward future considerations for human rights education research.